2021
DOI: 10.1016/s2665-9913(20)30378-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-exposure use of hydroxychloroquine on COVID-19 mortality: a population-based cohort study in patients with rheumatoid arthritis or systemic lupus erythematosus using the OpenSAFELY platform

Abstract: Background Hydroxychloroquine has been shown to inhibit entry of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) into epithelial cells in vitro, but clinical studies found no evidence of reduced mortality when treating patients with COVID-19. We aimed to evaluate the effectiveness of hydroxychloroquine for prevention of COVID-19 mortality, as opposed to treatment for the disease. Methods We did a prespecified observational, population-based cohort study usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 26 publications
3
47
0
3
Order By: Relevance
“…Hydroxychloroquine did not prevent illness compatible with COVID-19 when used as postexposure prophylaxis within 4 days after exposure [82]. As a further proof of the lack of efficacy of prophylactic use of hydroxychloroquine, a very recent observational population-based cohort study showed no evidence of a difference in COVID-19 mortality among people who received this drug for treatment of rheumatological disease before the COVID-19 outbreak in United Kingdom [83]. The RECOVERY trial found that, among 4716 patients hospitalised with COVID-19, hydroxychloroquine did not reduce 28-day mortality when compared to usual standard of care.…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 97%
“…Hydroxychloroquine did not prevent illness compatible with COVID-19 when used as postexposure prophylaxis within 4 days after exposure [82]. As a further proof of the lack of efficacy of prophylactic use of hydroxychloroquine, a very recent observational population-based cohort study showed no evidence of a difference in COVID-19 mortality among people who received this drug for treatment of rheumatological disease before the COVID-19 outbreak in United Kingdom [83]. The RECOVERY trial found that, among 4716 patients hospitalised with COVID-19, hydroxychloroquine did not reduce 28-day mortality when compared to usual standard of care.…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 97%
“…There are also conflicting results on whether patients taking hydroxychloroquine for the treatment of their rheumatic diseases are more likely to be infected with SARS-CoV-2. 80 , 81 A population-based cohort study including 30 569 patients with rheumatoid arthritis or systemic lupus erythematosus identified from a UK national primary care database (OpenSAFELY) 82 showed no difference in COVID-19-related mortality amongst hydroxychloroquine users versus non-users (HR 1·03, 95% CI 0·80 to 1·33). 82 Overall, the data do not support use of hydroxychloroquine in the context of COVID-19.…”
Section: Antirheumatic Drugs For the Management Of Covid-19mentioning
confidence: 99%
“…In contrast to these larger ‘positive’ reports, and other smaller reports of benefit, there have been several other observational studies which have not shown benefit in patients receiving hydroxychloroquine for rheumatological conditions, including another database analysis of 159 patients taking hydroxychloroquine compared with historical controls [ 58 ]. A publication reporting a large retrospective observational study using the OpenSAFELY platform, which comprises 40% of health records in the UK, and 30,569 patients with rheumatological conditions who had received ≥2 prescriptions of hydroxychloroquine in the previous 6 months found no difference in the COVID-19 mortality of hydroxychloroquine users [ 59 ]. These studies suffer variably from uncertain drug exposure, confounding by indication and underlying disease severity, as patients with milder rheumatological illness are normally started on drugs such as hydroxychloroquine and graduate to other medications with more severe illness.…”
Section: Antiviral Activitymentioning
confidence: 99%